Evaluation of the Level of Smart City Construction Based on Guangfo-Shenzhen-Dongguan in the Context of Guangdong-Hong Kong Macao Greater Bay Area. Issue 5 (25th May 2022) - M., M.; R., R.; Z., Z.; He, He; H., H.; Li, Li; S., S.; Cen, Cen; Y., Y.; Wu, Wu; Chu, H.; C., C.
No abstract available